Health care students’ views on Protecting Patients’ Privacy and Confidentiality (International Journal of Nursing Education, 2021)
In health care services, current technological advancements have made it easier to intervene witha person’s private life; thus, the need to ensure patients’ entitlement to privacy and confidentialityincreases.The study explores nursing and midwifery students’ perspectives on protecting patients’privacy and confidentiality through knowledge and insights gained from clinical experiences.The studywas conducted using a qualitative approach through focus group discussions with 48 first-year nursingand midwifery students from two nursing institutions in Brunei Darussalam. Three themes were derivedfrom the findings of the study: (1) Dignity of patients, (2) The values of privacy and confidentiality, and(3) Duty and everyone’s responsibility.The findings have shown that the students understand and knowthe value of privacy and confidentiality and agreed that protecting patients’ privacy and confidentialityare their moral duty and obligation.